Electrodeposition of Nickel matrix composite coatings via various Boride particles: A review - Dordsheikh Torkamani, Alireza; Velashjerdi, Mohammad; Abbas, Aqeel; Bolourchi, Mohammad; Maji, Pabitra (Journal of Composites and Compounds, 2021)
Composite electrodeposition or Electroplating is a process primarily applied in the industry through which metal substrates are coated with an additional phase, such as low-thickness films of a range of metals. Lately, the advent of coating based on metal matrix through deposition has been vital because the superior hardness has more improved wear and corrosion resistance than alloy-based or pure coatings of metal. Nickel is an engineering material, which has been broadly utilized for metal matrix applications. This paper summarizes recent research on the electrodeposition of nickel matrix composite coatings with borides ceramic particles. Some of these particles are ZrB2, BN, TiB2, Ni3B, CrB2, etc. in the nickel matrix. In addition, the most important results achieved in the field of these composite coatings were collected in this review.